Use of hepatoprotectors during tuberculosis chemotherapy: review of the Russian and international studies - A. A. Stаrshinovа; E. N. Belyaevа; A. M. Pаnteleev; M. V. Pаvlovа (Туберкулез и болезни лёгких)
The article presents the review of the Russian and international studies devoted to the use of hepatoprotectors during anti-tuberculosis treatment, including methionine derivatives and agents containing succinic acid.